Searches for BSM physics at a gamma-gamma collider with Energy < 12 GeV based on European XFEL - Berger Marten; Moortgat-Pick Gudrid; Wüst Monika (EPJ Web of Conferences)
The possibility of a Photon-Photon collider extension to the Beam dump of the 17.5 GeV European XFEL has been discussed before as the first high energy collider of its sort. It would not just be to study the concept of photon colliders but would also be a collider without competition in the region of 5 − 12 GeV for photon-photon collision. In this range, bb¯ and cc¯ resonances, tetraquarks as well as mesonic molecules can be observed. Furthermore, some BSM processes can also be reached in this range. In this paper we want to discuss the possibility of observing ALPs at such a collider. We will use a simplified description of the compton backscattering process to get a first look at cross sections and extend this to the full beam dynamics included prediction.